2020
DOI: 10.2174/1871520619666191211110640
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and Probiotic Biomass Loaded Pessaries for the Management of Cervical Cancer

Abstract: Introduction: Cancer is a type of disease, in which the growth of cells is abnormal and uncontrolled. One of the most common cancers among women is cervical cancer. In India, cervical cancer is one of leading causes of cancer mortality among women 30 to 69 years of age, accounting for 17% of all cancer deaths. The work present here shows the combined effects of anticancer drug along with probiotics to circumvent the side effects associated with chemotherapy and to enhance the therapeutic effect. Material and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In another meta-analysis ( Qiu et al., 2019 ) comparing the incidence of probiotics in the prevention of diarrhea caused by cervical cancer radiation therapy, the probiotics group had a lower incidence of RID, RR 0.61 (95% CI 0.46-0.81; P = 0.0007). Negi et al ( Negi et al., 2020 ) developed cisplatin and probiotic bioburden pessaries for the treatment of cervical cancer. Histopathological studies showed that the preparation was safe for local administration of cisplatin.…”
Section: Probiotics and Cervical Cancermentioning
confidence: 99%
“…In another meta-analysis ( Qiu et al., 2019 ) comparing the incidence of probiotics in the prevention of diarrhea caused by cervical cancer radiation therapy, the probiotics group had a lower incidence of RID, RR 0.61 (95% CI 0.46-0.81; P = 0.0007). Negi et al ( Negi et al., 2020 ) developed cisplatin and probiotic bioburden pessaries for the treatment of cervical cancer. Histopathological studies showed that the preparation was safe for local administration of cisplatin.…”
Section: Probiotics and Cervical Cancermentioning
confidence: 99%
“…For instance, cisplatin is a common therapy for CC; however, its toxicity affects normal cells and tissues. Negi et al [ 116 ] combined cisplatin with probiotic-loaded pessaries (Lactobacillus rhamnosus) in a vaginal mouse model. They found a better outcome with fewer side effects of cisplatin and a reduced tumor volume in the treated group.…”
Section: Bacteriotherapy In Cervical Cancer Treatmentmentioning
confidence: 99%
“…Probiotics were also used for their anticancer activities in cervical cancer via activating the maturation of natural killer cells and promoting cellular and humoral immunity. Additionally, probiotics were added to reduce the side effects of radiation therapy for cervical malignancies[ 25 ].…”
Section: To the Editormentioning
confidence: 99%